NON-AGRICULTURAL BUSINESS ACTIVITY OF PRIVATE FARMS - Zajdel, Małgorzata (Acta Scientiarum Polonorum. Oeconomia, 2006)
The aim of the paper was to define changes which occurred in the non-agricultural business activity of farms between the agricultural censuses of 1996 and 2002. As provided for in the working hypothesis, it was found that changes in the non-agricultural business activity were more intensive on small farms rather than the medium-size and large ones. Taking up the non-agricultural business activity was mainly driven by the need to satisfy the every-day living and material needs of the family, and much less considerably by the intention to become professionally active beyond the agricultural farm.